Trunk extensors endurance with arms parallel to the trunk is superior to other arms positions: randomized- controlled trial - Samiha Mohamed Ibrahim Abd Elkader; Abdullah Mohamed Yehia Al-Shenqiti; Tarek Mohamed Fathi El-Gohary (Journal of the Pakistan Medical Association, 2022)
Abstract Objective: To compare the effect of arms positions on the static endurance ability of trunk extensors, and to investigate the effect of home endurance training of trunk extensors on isokinetic outputs. Method: The prospective, randomised, assessor-blinded, controlled- intervention study was conducted from December 2017 to October 2019 at the College of Medical Rehabilitation Sciences, Taibah University, Madinah, Saudi Arabia, and comprised males aged 20-24 years who were randomly assigned to one of the four groups. Group A had their hands above the head, group B had their hands behind the head, group C had their hands parallel to their trunk, and group D had their hands on the chest. Data was collected at baseline, and after 6 and 8 weeks of static trunk extensors endurance training. Isokinetic outputs of peak torque and average power were also measured. Data was analysed using SPSS 23. Results: Of the 60 participants, 15(25%) were in each of the four groups. The overall mean age was 22.02±1.2 years. At baseline, there was no significant difference among the groups (p>0.05). There was significant intra-group improvement for all outcome variables after 6 and 8 weeks of training (p<0.05). Conclusion: Static endurance of the trunk extensors with having arms parallel to the trunk was superior to other arm positions, especially after six and eight weeks of training but didn’t affect the isokinetic outputs. Clinical Trial Number: (NCT03107676) Key Words: Arms positions, Healthy subjects, Trunk endurance, Trunk extensors.